Management of Shock Recent Advances - Agrawal, Amit; Waindeskar, Vaishali (IntechOpen, 2023)
Recent advancements have resulted in improved diagnosis and management of patients who present with shock in clinical practice. Shock can lead to decreased tissue perfusion and thus decreased oxygenation, resulting in poorer outcomes. Timely diagnosis and appropriate interventions are crucial to break the cascade of events and thus improve outcomes in patients with shock. This book presents a comprehensive overview of shock, including information on its etiology, detection, and management.